Pemanfaatan Lahan di bawah Tegakan Kelapa di Lampung - Junita Barus (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2013)
Lampung is one of the central areas of coconut plantations in Indonesia, covering an area of about 126,129 ha.Â Approximately 80% of land under coconut can be used for other crops and livestock. Types of plants that can be cultivated in between coconut plants (intercrops) include perennial crops such as cocoa and banana, annual crops such as corn, soybeans and upland rice, depending on the local climate and soil conditions. Constraints in land use under the coconut tree were solar radiation and soil fertility (low fertility soil as a growing medium). Dry land in Lampung is generally acidic soil with a pH below 5 in which the availability of nutrients, especially P is low. Efforts should be made to improve the fertility of the land, including the application of inoculum solvent phosphate on acid soils, the use of organic fertilizers and bio-fertilizers with the right dose according to the condition of the land. Observations were conducted at several villages which the centers of coconut plantations in the South Lampung regency.Â In these villages, only about 30% of the total area under coconut trees was used for intercrops. Types of plants for intercrops were maize, bananas, and upland rice.